1984
DOI: 10.1002/ajmg.1320190307
|View full text |Cite
|
Sign up to set email alerts
|

Variable patterns of malformation in the mouse fetal hydantoin syndrome

Abstract: Controversy over the existence of a fetal hydantoin syndrome continues in medical literature despite numerous recent clinical studies describing additional patients with a characteristic pattern of abnormalities. Resistance to its acceptance as a clinical entity seems to stem from the variability of the component malformations seen in this syndrome. To examine this variability in a controlled experimental situation, we utilized data obtained in previously reported studies of a mouse model of the fetal hydantoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Regardless of the route of administration, orally or parenterally, PHT adversely affects the process of embryogenesis in a number of different species, including the mouse, rat, rabbit, cat and monkey [Harbison and Becker, 1969, 1972; Khera, 1979; McClain and Langhoff, 1980; Mercier-Parot and Tuchmann-Duplessis, 1974]. Since the early human clinical studies reported an increase in the incidence of cleft lip and/or cleft palate among the offspring of epileptic patients, the vast majority of experimental studies on the teratogenicity of PHT have focused on the ability of this compound to induce orofacial clefts [Abela et al, 2005; Elshove, 1969; Finnell and Chernoff, 1984; Sulik et al, 1979]. Results of these studies showed that the lowest dose of PHT able to induce cleft palate in susceptible mouse strains was 12.5 mg/kg/day administered to the pregnant dam during the period of palate formation.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Regardless of the route of administration, orally or parenterally, PHT adversely affects the process of embryogenesis in a number of different species, including the mouse, rat, rabbit, cat and monkey [Harbison and Becker, 1969, 1972; Khera, 1979; McClain and Langhoff, 1980; Mercier-Parot and Tuchmann-Duplessis, 1974]. Since the early human clinical studies reported an increase in the incidence of cleft lip and/or cleft palate among the offspring of epileptic patients, the vast majority of experimental studies on the teratogenicity of PHT have focused on the ability of this compound to induce orofacial clefts [Abela et al, 2005; Elshove, 1969; Finnell and Chernoff, 1984; Sulik et al, 1979]. Results of these studies showed that the lowest dose of PHT able to induce cleft palate in susceptible mouse strains was 12.5 mg/kg/day administered to the pregnant dam during the period of palate formation.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Regardless of the route of administration, orally or via injection, PHT disrupts normal embryonic development in a number of different species, including the mouse, rat, rabbit, cat and monkey [9498]. The vast majority of experimental studies on the teratogenicity of PHT have focused on the ability of this compound to induce orofacial clefts, reflecting the early human clinical reports of an increase in the incidence of cleft lip and/or cleft palate among the offspring of epileptic patients [99102]. These studies demonstrated that cleft palate can be induced in susceptible mouse strains when doses as low as 12.5 mg/kg/day are administered to the pregnant dam during the sensitive period for palate closure.…”
Section: Mechanisms Of Aed Teratogenicitymentioning
confidence: 99%
“…There is ample evidence that phenytoin is a developmental toxicant in animals and humans. The fetal hydantoin syndrome in humans is characterized by facial dysmorphologies, growth retardation, and other anomalies (98,133), and similar effects have also been seen in rodents (134). Animal studies have also shown that perinatal administration of phenytoin causes a reduction in brain weight (135) and a number of behavioral deficits (seen at subteratogenic doses), which include, in particular, deficits in spatial learning tasks and activity change (hyperactivity) (136)(137)(138).…”
mentioning
confidence: 95%